2002
DOI: 10.1021/ja0041831
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropylcarbinyl-Type Ring Openings. Reconciling the Chemistry of Neutral Radicals and Radical Anions

Abstract: Cyclopropylcarbinyl --> homoallyl and related rearrangements of radical ions (a) are frequently used as mechanistic "probes" to detect the occurrence of single electron transfer in chemical and biochemical processes, (b) provide the basis for mechanism-based drug design, and (c) are important tools in organic synthesis. Unfortunately, these rearrangements are poorly understood, especially with respect to the effect of substrate structure on reactivity. Frequently, researchers assume that the same factors which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 79 publications
1
74
0
3
Order By: Relevance
“…Recent research, notably by Tanko and co-workers, has shown that this assumption is not valid as both charge and spin are governing factors in the reactivity of radicalanion rearrangements. [2,3] There are a number of examples involving the rearrangements of radical anions in which bond cleavage results in formation of a single species containing a spatially separated radical and anion [Eq. (1)].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research, notably by Tanko and co-workers, has shown that this assumption is not valid as both charge and spin are governing factors in the reactivity of radicalanion rearrangements. [2,3] There are a number of examples involving the rearrangements of radical anions in which bond cleavage results in formation of a single species containing a spatially separated radical and anion [Eq. (1)].…”
Section: Introductionmentioning
confidence: 99%
“…[ 35] The results summarized in Table 4 indicate that under the mild conditions used the Ti-catalyzed procedure is compati- ble with different functional groups, including alkyl halides, phenols, and ketals. Moreover, the easy lactonization that occurred after the allylation of keto ester 43 suggested that this procedure might become a useful tool for the synthesis of g-lactones.…”
Section: Resultsmentioning
confidence: 99%
“…However, a body of work by Tanko and coworkers has provided evidence that this assumption is not necessarily valid. [3][4][5][6] They demonstrated by electrochemically generating a series of cycloalkylketone radical anions that both charge and spin are governing factors in the reactivity of radical-anion rearrangements. The radical anions in these studies were observed to undergo a carbon-carbon bond fragmentation yielding a single species containing a spatially separated radical and anion, which is otherwise known as a distonic radical anion [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies between the rates constants for fragmentation of radical-anions and their neutral radical counterparts are only recently becoming known. [3,4,7,8] For the fragmentation of 2 a, it is suggested that the alkoxyl anion is more readily stabilized by the aryl rings than the alkoxyl radical center. This assessment agrees with the trend in the fragmentation rate constants as 2 d has the lowest value as the 4-nitrophenyl rings provide the greatest stabilizing effect on the alkoxide anion.…”
mentioning
confidence: 99%